The Damascus events : the 1860 massacre and the making of the modern Middle East - Rogan, Eugene, 1960- (Basic Books, 2024)
"On July 9, 1860, a violent mob swept through the Christian quarters of Damascus. For eight days, violence raged, leaving five thousand Christians dead, thousands of shops looted, and churches, houses, and monasteries razed. The sudden and ferocious outbreak shocked the world, leaving Syrian Christians vulnerable and fearing renewed violence. Drawn from never-before-seen eyewitness accounts of the Damascus Events, eminent Middle East historian Eugene Rogan tells the story of how a peaceful multicultural city came to be engulfed in slaughter. He traces how rising tensions between Muslim and Christian communities led some to regard extermination as a reasonable solution. Rogan also narrates the wake of this disaster, and how the Ottoman government moved quickly to retake control of the city, end the violence, and reintegrate Christians into the community. These efforts to rebuild Damascus proved successful, preserving peace for the next 150 years until 2011. The Damascus Events offers a vivid history, one that masterfully uncovers the outbreak of violence that unmade a great city and examines the possibility, even after searing conflict and unimaginable tragedy, of repair"--